Microbiological analysis of Greek Protected Designation of Origin cheeses and characterisation of the isolated lactic acid bacteria. (December 2021) - Rhoades, Jonathan; Anastasiou, Iro; Michailidou, Sofia; Koinidis, Antonis; Doulgerakis, Christos; Alexa, Elena A.; Alvarez-Ordóñez, Avelino; Argiriou, Anagnostis; Likotrafiti, Eleni
Abstract: The microbiological characteristics of Greek Protected Designation of Origin (PDO) cheeses were determined and isolated bacteria were investigated. Six cheese types were examined: Anevato, Batzos, Feta, Galotyri, Kalathaki Limnou and Kopanisti. The highest levels of faecal indicator bacteria, presumptive Listeria spp. and presumptive Staphylococcus aureus were all recorded in Batzos cheese, and the lowest in Feta and Kopanisti. Of the 35 isolates examined with 16S rRNA sequencing, 26 were Lactobacillus spp., eight were Enterococcus spp. and one was Pediococcus parvulus . Of 30 isolates investigated, 86.7% grew well on galactooligosaccharides, while 66.7% grew well on fructooligosaccharides. Cell-free culture supernatants (pH 6) of 14 isolates were inhibitory against some or all of Salmonella Typhimurium, Listeria monocytogenes and Escherichia coli . This research demonstrates that Greek PDO cheeses are of variable microbiological quality and are a rich source of potentially useful bacteria that can be used as antimicrobial synbiotics or biopreservative cultures.